Interaction between gelatin and sodium dodecyl sulfate at the air/water interface: A neutron reflection study - Cooke, D; Dong, C; Thomas, R; Howe, A; Simister, E; Penfold, J (ACS, 2000)
Neutron reflection has been used to study the composition and structure of layers adsorbed at the air/water surface of solutions of gelatin and sodium dodecyl sulfate (SDS) and these results have been compared with the surface tension of the same solutions. Above a concentration where free micelles of SDS can be expected to form in the bulk solution the layer is exactly as would be expected for solutions of SDS on its own. However, at low SDS concentrations the presence of gelatin greatly enhances the adsorption of SDS in comparison with solutions just containing surfactant, and in the intermediate range of SDS concentration, where the surface tension is relatively constant, the surface excess of SDS is also constant at gelatin concentrations of 0.1 wt%. The thickness of the surfactant layer in the two lower ranges of SDS concentration is much larger than a simple surfactant layer, ranging from 35 down to 22 angstroms (in comparison with 19 angstroms for the pure surfactant layer), suggesting that the layer is not only roughened by binding of gelatin at the surface but that a proportion of the bound SDS molecules are completely immersed just below the surface. This is confirmed by measurements of the layer structure at different isotopic compositions. The presence of gelatin at the surface and the enhancement of the adsorption of SDS indicate that complexes of gelatin and SDS are strongly surface active. Furthermore, the measured thickness of the SDS layer at the surface shows that these complexes probably do not contain surfactant in the form of micelles. This further suggests that it may not be reliable to interpret the first discontinuity in the surface tensionlog(concentration) plot in such strongly interacting systems as the point at which there is an onset in aggregation of the surfactant on the polyelectrolyte (critical aggregation concentration, or CAC).